MOTIVASI BELAJAR SISWA PADA KOMPETENSI DASAR MEMBUAT BUSANA PESTA JURUSAN TATA BUSANA DI SMK NEGERI 1 TEBO - Trapulisa, Juli; Ramainas, Ramainas; Izwerni, Izwerni (Journal of Home Economics and Tourism, 2013)
The background of this research are (1) the lack motivation of the students in doing basic competence making the party dress (2) there are some students have the score under minimum achievement criteria. This research aimed to (1)describe how high the motivation of the students in making party dress for the persevering, (2) describe how high the motivation of the students in making party dress for the ductile, (3) describe how high the motivation of the students in making party dress for not getting bored quickly. The kind of this research is quantitative descriptive. The population is all students of XII degree of fashion SMK N 1 Tebo which are 24 students. All population is the sample. Data analysis did by determining presentation, chategorize and respondents total achievement. The result shows that 54% students of XII degree SMK N 1 Tebo have the middle persevering, 46% students of XII degree SMK N 1 Tebo have the middle ductile, and 50% students of XII degree SMK N 1 Tebo have the low attitude for not getting bored quickly, generally, 42% students of XII degree SMK N 1 Tebo have the middle learning motivation.Keywords: Motivation, Competence, Fashion PartyA. PENDAHULUAN